Wip1 regulates Smad4 phosphorylation and inhibits TGF‐β signaling - Park, Dong‐Seok (EMBO Rep, 2020)
The tumor suppressor Smad4, a key mediator of the TGF‐β/BMP pathways, is essential for development and tissue homeostasis. Phosphorylation of Smad4 in its linker region catalyzed by the mitogen‐activated protein kinase (MAPK) plays a pivotal role in regulating its transcriptional activity and stability. In contrast, roles of Smad4 dephosphorylation as a control mechanism of TGF‐β/BMP signaling and the phosphatases responsible for its dephosphorylation remain so far elusive. Here, we identify Wip1 as a Smad4 phosphatase. Wip1 selectively binds and dephosphorylates Smad4 at Thr277, a key MAPK phosphorylation site, thereby regulating its nuclear accumulation and half‐life. In Xenopus embryos, Wip1 limits mesoderm formation and favors neural induction by inhibiting TGF‐β/BMP signals. Wip1 restrains TGF‐β‐induced growth arrest, migration, and invasion in human cells and enhances the tumorigenicity of cancer cells by repressing the antimitogenic activity of Smad4. We propose that Wip1‐dependent dephosphorylation of Smad4 is critical for the regulation of TGF‐β signaling.